Temporal distribution of, and effect of anthropic modifications on, phlebotomine populations in the Chaco Bioregion, Argentina - Szelag, Enrique Alejandro (2017)
The Phlebotominae (Diptera: Psychodidae) are insects of medical andveterinary importance, because some species are able to transmitpathogens such as Leishmania sp. In the last 20 years, the ChacoBioregion (Argentina) has reported numerous leishmaniasis outbreaks, withan increasing trend of cases associated with periurban transmission. TheChaco Bioregion has two sub-regions according to their climatic andecological characteristics: the Dry Chaco and the Humid Chaco. In thepresent study, we performed phlebotomine captures in both sub-regions,at sites with different level of anthropic modifications, with the aim todescribe differential spatio-temporal patterns of potential tegumentary andvisceral leishmaniasis vectors. The captures yielded 3559 phlebotomine offourteen species. Migonemyia migonei was the prevalent species in the DryChaco, whereas Mg. migonei and Nyssomyia neivai were co-dominant inthe Humid Chaco. Environmental factors such as degree of anthropicmodification and climatic factors were found to modulate both thephlebotomine fauna composition and the diversity and abundance of eachspecies. These conditions would increase vector abundances, and thus thetransmission risk, during warm months with moderate rainfall, especially inareas with higher anthropic modifications. The co-dominance patternsobserved in transitional areas could contribute to the transmission ofleishmaniases.